Car advertisement online system (CAOS) / Mohamad Helmi Ahmad Zaiki - Ahmad Zaiki, Mohamad Helmi (2007)
As the world has moving towards the technology era, all kind of service industries have started to upgrade their performance using computer and technology. Many web based application system have been online nowadays in andMotortrader.com.my is one of the online application services that provide web based application system for online car advertising. Nowadays, most system management is being delivered through computer, software and application. In Malaysia, the usage of internet as a medium for advertising is not a new things, but as a car online advertising system, it not a popular medium, and car online advertising system have a potential to conquers a car advertising markets.